2015
DOI: 10.1002/2014jc010557
|View full text |Cite
|
Sign up to set email alerts
|

Water mass pathways to the North Atlantic oxygen minimum zone

Abstract: The water mass pathways to the North Atlantic Oxygen Minimum Zone (naOMZ) are traditionally sketched within the cyclonic tropical circulation via the poleward branching from the eastward flowing jets that lie south of 10 N. However, our water mass analysis of historic hydrographic observations together with numerical Lagrangian experiments consistently reveal that the potential density level of r h 5 26.8 kg m 23 (r26.8, approximately 300 m depth) separates two distinct regimes of circulation within the Centra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
66
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(75 citation statements)
references
References 66 publications
9
66
0
Order By: Relevance
“…It intensified during the relaxation season. The observed opposing flow regimes in the two central water layers compare well with the results obtained by Peña‐Izquierdo et al () who suggested by analyzing hydrographic data and the output of an assimilation model opposing circulation cells in the upper and lCW layers. Equatorward flow below the poleward eastern boundary currents was also observed in the upwelling region off Peru (e.g., Chaigneau et al, ) and off Angola (Tchipalanga et al, ), suggesting that it is a common feature of EBC.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…It intensified during the relaxation season. The observed opposing flow regimes in the two central water layers compare well with the results obtained by Peña‐Izquierdo et al () who suggested by analyzing hydrographic data and the output of an assimilation model opposing circulation cells in the upper and lCW layers. Equatorward flow below the poleward eastern boundary currents was also observed in the upwelling region off Peru (e.g., Chaigneau et al, ) and off Angola (Tchipalanga et al, ), suggesting that it is a common feature of EBC.…”
Section: Discussionsupporting
confidence: 90%
“…Meridional sections taken during two successive upwelling/relaxation cruises further suggest that ventilation of the uCW and lCW layers occurs from the south and north, respectively. This has previously been proposed through modeling studies by Elmoussaoui et al () and Peña‐Izquierdo et al () and was inferred from observed hydrographic properties and oxygen distributions by Voituriez and Chuchla (). Waters high in SACW concentration advected from the south in the uCW layer, and waters high in NACW concentration from the north in the lCW layer were both higher in oxygen concentrations with respect to ambient waters.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…7 and S2 in supplemental materials). The anomaly linear regression is set predominantly by the data in the eastern basin, influenced by the African upwelling where major remineralization processes take place (Peña-Izquierdo et al 2015). The data from the western basin shows little dependence of the F(340/440) anomalies on NO 3 and AOU, probably as a consequence of input of humic-organic-matter sediments.…”
Section: Discussionmentioning
confidence: 99%